An appreciation of Tom Wilson - Amanda Cossham (Information Research: An International Electronic Journal)
Tom Wilson’s information behaviour and information retrieval research and his stellar publishing record make him one of the most significant figures in library and information studies. One aspect that may be less well-known is his kindness and generosity towards new and emerging researchers and more junior colleagues. This short piece talks about his willingness to support those researchers, to provide advice, to be interviewed, to give of his time and expertise to foster the development and engagement of them within the profession.